Análise dos efeitos de segunda ordem globais de torção em edifícios altos em concreto - Sonda, Eduardo da Luz (2023)
Tall concrete buildings may have their structural behavior significantly influenced by global second-order effects, resulting from geometric non-linearity, depending on certain characteristics of the building. The evaluation of second-order effects can be performed, according to NBR 6118:2014, through the γz coefficient, proposed by Franco and Vasconcelos (1991). Such procedure, widely disseminated and consolidated in structural analyses of buildings, is a simple and efficient tool for evaluating second-order effects about horizontal displacements of buildings with small displacements. However, when dealing with secondorder effects due to rotational displacements, little is known about its possible limitations. Franco (2003) presents a possibility of simplified analysis of second-order effects due to rotational displacements, using the γθ coefficient. The analysis procedure for this parameter is analogous to that of the γz coefficient, however, it is not yet widespread in the technical field. In this way, the current study analyzed and discussed the torsional effects in buildings according to the γθ parameter, as well as analyzed structural models of different multi-story buildings, with varied shapes and bracing characteristics, to verify their efforts and displacements, with the help of the TQS software, applying the established methodologies for the global analysis of buildings, as well as the γθ parameter. Thus, the influence of different parameters and characteristics of the coefficient on the overall stability of buildings was verified, as well as the importance of considering rotational second-order effects in tall buildings, in addition to presenting the methodology for analyzing and calculating the rotational second-order effects for application in structural design of buildings. Through the analysis of 6 structural models of buildings, different methodologies for calculating the position of the floor’s center of twist were analyzed, and it was verified that the methodology developed by Franco (2003) is the most applicable to the reality of structural projects in Brazil. Based on the analysis of 16 more models developed to evaluate the global second-order effects of torsion, it was possible to verify the influence of different geometries in plans and heights in addition to the position and direction of elements of high stiffness in the γθ parameters and γz of different modeled buildings. Thus, it was possible to verify a direct relationship between the height of the studied buildings and the global second-order effects due to torsion. It was possible to note that, for the analyzed models, the orientation of the structural core in the plan view was more influential in the secondorder effects due to torsion than its position. It was also concluded that the results of the γθ and γz coefficients do not show the same behavior in different situations, indicating that the consecrated and important parameter γz does not satisfactorily represent second-order torsion effects, thus the γθ coefficient is an applicable parameter for such analysis.